Kinetic modeling and optimization of parameters for biomass pyrolysis: A comparison of different lignocellulosic biomass. Issue 14 (18th July 2019) - Mahmood, Hamayoun; Ramzan, Naveed; Shakeel, Ahmad; Moniruzzaman, Muhammad; Iqbal, Tanveer; Kazmi, Mohsin Ali; Sulaiman, Muhammad
ABSTRACT: A primitive element for the development of sustainable pyrolysis processes is the study of thermal degradation kinetics of lignocellulosic waste materials for optimal energy conversion. The study presented here was conducted to predict and compare the optimal kinetic parameters for pyrolysis of various lignocellulosic biomass such as wood sawdust, bagasse, rice husk, etc., under both isothermal and non-isothermal conditions. The pyrolysis was simulated over the temperature range of 500–2400 K for isothermal process and for heating rate range of 25–165 K/s under non-isothermal conditions to assess the maximum pyrolysis rate of virgin biomass in both cases. Results revealed that by increasing the temperature, the pyrolysis rate was enhanced. However, after a certain higher temperature, the pyrolysis rate was diminished which could be due to the destruction of the active sites of char. Conversely, a decrease in the optimum pyrolysis rate was noted with increasing reaction order of the virgin biomass. Although each lignocellulosic material attained its maximum pyrolysis rate at the optimum conditions of 1071 K and 31 K/s for isothermal and non-isothermal conditions, respectively, but under these conditions, only wood sawdust exhibited complete thermal utilization and achieved final concentrations of 0.000154 and 0.001238 under non-isothermal and isothermal conditions, respectively.